COST-EFFECTIVENESS ANALYSIS OF CEFTRIAXONE AND CEFIXIME IN TYPHOID FEVER PATIENTS HOSPITALIZED AT BERKAH PANDEGLANG REGIONAL HOSPITAL FOR THE PERIOD 2020-2021 - Yusransyah Yusransyah; Yuni Rahmawati; Baha Udin; Nia Marlina Kurnia (Jurnal Farmasi Sains dan Praktis, 2023)
Typhoid fever is an infectious disease among humans caused by the bacterium Salmonella typhi. With the high Multi-Drug Resistance (MDR) of Salmonella typhi, selecting the right antibiotic is a factor that must be considered in addition to cost constraints. Therefore, cost-effectiveness is needed. This study aims to determine the cost-effectiveness of typhoid fever patients using ceftriaxone and cefixime antibiotics. The data used are retrospective, and the sampling was done by purposive sampling. This study was conducted at Berkah Pandeglang Regional Hospital. Sample in this study, namely typhoid fever patients of the period 2020-2021, who meet the inclusion and exclusion criteria. In this study, 16 samples were obtained. The results of this study showed that the total average direct medical costs for the ceftriaxone group were IDR 78.632.500 In contrast, the cefixime group was IDR 75.527.300. The ACER value of typhoid fever patients who used Ceftriaxone + cefixime was IDR 91,646.27, Ceftriaxone was IDR 77,463.89, and cefixime was IDR 88,027.15. The patients with typhoid fever who used Ceftriaxone were more cost-effective than those who used Cefixime